Pengaruh Citra Merk, Promosi Dan Harga Terhadap Loyalitas Pelanggan Hp Samsung (Studi Pada Mahasiswa Manajemen 2019 Universitas Islam Malang) - Bachtiyar, Riski; Wahono, Budi; Mustapita, Arini Fitria (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Along with economic growth and technological developments, the business world is experiencing rapid development with the emergence of various companies trying to create products and quality offered at competitive prices, which are potential producers to consider purchasing decisions of consumers. This study aims to investigate the impact of product quality, price, and digital marketing on consumer interest in purchasing Roughneck 1991 goods. This study uses a quantitative approach. Data collection techniques were carried out using a questionnaire through the Google form and measured using a Likert scale. The sample in this study were 95 respondents who were taken from the technique using the Malhotra formula. Furthermore, after the data is collected, to test the hypothesis using SPSS software. The results of the study show that digital marketing, product quality, and price have a significant effect on the intention to buy Roughneck 1991 products. Keywords: Digital Marketing, Product Quality, Price, Purchase Intention